Estimating Air Travel Demand in North Sumatra Using Gravity Model Approach with Economic and Route Analysis - Zulkarnain, Ahnis; Pasaribu, Hisar Monongam; Sembiring, Javensius (Langit Biru: Jurnal Ilmiah Aviasi, 2025)
This study estimates regional air travel demand in North Sumatra Province using variations of the gravity model. The objectives are to identify key factors influencing air travel demand, estimate demand through different model formulations, and assess airport infrastructure adequacy for regional connectivity. Three models were developed, progressively incorporating economic indicators such as GDP per capita, population, and distance, alongside socio-economic variables like leisure attractions, hotel accommodations, universities, and health facilities. The methodology involved log-linear transformations and regression analysis to estimate parameters. Results revealed significant variability in air travel demand, driven by proximity and economic activity, with the population coefficient shifting from 0.707 in Model 1 to -0.178 in Model 3, as socio-economic variables like leisure attractions (0.811) and GDP per capita (0.813) became more influential. Findings also exposed disparities in airport coverage, highlighting the need for strategic infrastructure improvements, particularly for high-demand pairs like Medan - Mandailing Natal.